Bactericidal effect of zinc oxide nanoparticles on Grampositive and Gram-negative strains in reverse spin bioreactor. Issue 1 (January 2021) - Rutherford, D; Jíra, J; Kolářová, K; Remeš, Z; Rezek, B
Abstract: We present an experimental study investigating the efficacy of zinc oxide nanoparticle use for bacterial decontamination of water using reverse spin technology. The number of viable bacteria reduced with treatment time and the rate of inactivation was dependent on zinc oxide concentration. Gram-positive S. aureus bacteria were more resistant to zinc oxide nanoparticles compared to Gram-negative E. coli, however both strains were completely eradicated after 4 hours using a concentration of 10 μg/mL. Nanoparticles did not inhibit growth of bacteria when added to an agar surface, neither when in liquid before bacteria inoculation nor when loaded onto filter paper disks after bacteria inoculation. These results emphasise the importance of efficient reactor mixing to enhance interaction capability for ZnO use in water decontamination.